2020
DOI: 10.1111/jeb.13672
|View full text |Cite
|
Sign up to set email alerts
|

Ecological fitting is the forerunner to diversification in a plant virus with broad host range

Abstract: The evolution and diversification of ssRNA plant viruses are often examined under reductionist conditions that ignore potentially much wider biotic interactions. The host range of a plant virus is central to interactions at higher levels that are organized by both fitness and ecological criteria. Here we employ a strategy to minimize sampling biases across distinct plant communities and combine it with a high‐throughput sequencing approach to examine the influence of four habitats on the evolution of Watermelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Similarly, SMV sequences identified from the Pinellia species in China showed the highest number of both segregating sites and total number of mutations compared to other plant hosts, including G. max and G. soja . Based on these results, we suppose that the expansion of plant hosts might affect the genetic diversity of SMV CP sequences, as previously suggested [ 28 ].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, SMV sequences identified from the Pinellia species in China showed the highest number of both segregating sites and total number of mutations compared to other plant hosts, including G. max and G. soja . Based on these results, we suppose that the expansion of plant hosts might affect the genetic diversity of SMV CP sequences, as previously suggested [ 28 ].…”
Section: Discussionsupporting
confidence: 78%
“…Melon is one of the main horticultural crops in Spain, and viral diseases can threaten its production. Among the different viruses reported to infect melon ( 28 , 29 , 31 , 32 ), CABYV seems to be the most prevalent virus followed by WMV ( 7 , 15 , 18 ). In our case, we found that WMV was the prevalent virus in melon crops followed by CABYV; this discrepancy may be due to an actual change in the relative prevalence of the viruses in the area, but also to the sample size or even to the different methods used for detection, perhaps with different sensitivities for the two viruses.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study comparing the diversity of viral populations between tomato plants and neighboring Solanum nigrum plants using HTS showed a large variability in virome richness, but with little overlap of the viruses found in both species ( 6 ). In another study, authors examined the influence of four different habitats on the evolution of watermelon mosaic virus (WMV), reporting that the WMV genetic diversity was structured by habitat types and host species ( 7 ). Also, Juárez et al ( 8 ) showed that the tomato leaf curl New Delhi virus (ToLCNDV) population infecting Datura stramonium in Spain displayed higher levels of within-host genetic diversity when compared to crops ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been recently shown to induce a long-lasting silencing of PDS in watermelon, melon, cucumber, and bottle gourd (Liu et al 2020). Although we have only performed experiments on melon, because WMV presents a broad host range-160 dicotyledonous species of 23 families (Desbiez and Lecoq 2004;Ouibrahim et al 2014;Peláez et al 2020)-we expect this new system to be useful in other cucurbits, as well as species outside this family that also host the virus. The vector is based on a single binary plasmid carrying kanamycin resistance, as well as two origins of replication in E. coli and A. tumefaciens.…”
Section: Discussionmentioning
confidence: 99%